Islamic Education and Social Transformation: Teenager Corruption Watch (TCW) Modelling in Islamic School - Mukodi Mukodi (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Nowadays, corruption is one of Indonesias acute problems. It seems to have infected and spread to everyone. It influences every aspect of human lives and social elements. Therefore, it ruins the human civilization. The nations basis and nationsstrength become weak. The researcher used descriptive qualitative survey method to explain how Teenager Corruption Watch (TCW) modeling overcomes the corruption problems early in this country. The researchs results are as follows: first, Islamic insight (Islamic transformative) can be used effectively as a basic point in implementing TCW in Islamic schools. Second, the existence of TCW can be an organization for anti rasyuwah in Islamic schools. Third, the TCW model in Islamic schools consists of three forms, such as (a) TCW-based extracurricular, (b) TCW-based intracurricular, and (c) top-down applicative TCW.